2018
DOI: 10.1371/journal.pone.0204945
|View full text |Cite
|
Sign up to set email alerts
|

Survey on opinions and usage patterns for the ResearchGate platform

Abstract: Based on a survey, the following study investigates opinions and also usage patterns relating to the ResearchGate social networking site for scientists and researchers. The survey consisted of 19 questions and was conducted online with 695 scientists from the disciplines of physics, biology, medicine, and neuroscience. Amongst other issues, the research questions concerned how much time and effort the interviewees expended on ResearchGate, what added value they perceived in using the site, the extent to which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 8 publications
(10 reference statements)
0
22
0
1
Order By: Relevance
“…Further, they were seldom used for discussion or interaction, as evidenced by the fact that only 6 questions were asked or answered among the 81 researchers who have a profile in ResearchGate, which aligns with findings in previous literature. Meier and Tunger (2018) found that only 19% of ResearchGate users in physics, biology, medicine, and neuroscience had asked a question, and 49% had provided an answer. Shrivastava and Mahajan (2017) also found that only 12% of the physics researchers in an Indian university asked or answered a question.…”
Section: Discussionmentioning
confidence: 99%
“…Further, they were seldom used for discussion or interaction, as evidenced by the fact that only 6 questions were asked or answered among the 81 researchers who have a profile in ResearchGate, which aligns with findings in previous literature. Meier and Tunger (2018) found that only 19% of ResearchGate users in physics, biology, medicine, and neuroscience had asked a question, and 49% had provided an answer. Shrivastava and Mahajan (2017) also found that only 12% of the physics researchers in an Indian university asked or answered a question.…”
Section: Discussionmentioning
confidence: 99%
“…There are examples of scientific fraud detection that led to retractions of articles thanks to this resource. 10 Furthermore, certain platforms, the primary purpose of which is other, allow post-publication peer review, among them Researchgate, 11 a social network that is widely used by researchers, where users can comment on articles other authors post on their personal profiles. Publons 12 is a platform designed to build a researcher's profile, where scientific production is incorporated in terms of articles, patents, as well as post-publication reviews of literature generated by other researchers.…”
Section: Journals and Platforms With Post-publication Peer Reviewmentioning
confidence: 99%
“…Likewise, access to scientific information is undergoing profound transformations due to the emergence of new channels for the dissemination of research papers, such as repositories and social networks such as ResearchGate (Meier;Tunger, 2018). In addition, there are illegal platforms that offer access to millions of publications, such as Sci-Hub (Nicholas et al, 2019).…”
Section: Fundingmentioning
confidence: 99%